2009
DOI: 10.1017/s1368980009992072
|View full text |Cite
|
Sign up to set email alerts
|

Validation of nutrient intake using an FFQ and repeated 24 h recalls in black and white subjects of the Adventist Health Study-2 (AHS-2)

Abstract: Objective To validate a 204-item quantitative FFQ for measurement of nutrient intake in the Adventist Health Study-2 (AHS-2). Design Calibration study participants were randomly selected from the AHS-2 cohort by church, and then subject-within-church. Each participant provided two sets of three weighted 24 h dietary recalls and a 204-item FFQ. Race-specific correlation coefficients (r), corrected for attenuation from within-person variation in the recalls, were calculated for selected energy-adjusted macro- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
150
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(166 citation statements)
references
References 23 publications
14
150
0
2
Order By: Relevance
“…For unadjusted nutrients the validity and calibration coefficients tended to be higher for men than women, however after energy adjustment the differences between men and women were reduced (7) . In the NIH-AARP study, validity coefficients for energy-adjusted nutrients ranged from 0·36 to 0·76, and the calibration coefficients from 0·24 to 0·68, which compared well with results of three other validation studies reviewed by the authors (28)(29)(30) and are slightly lower than the ranges that we observed in Australian-born participants; although all these studies are likely to overestimate the validity of the test instrument. Among the Australian-born, intakes of retinol equivalents (defined as vitamin A expressed as retinol equivalents = retinol + β-carotene/6 + α-carotene/12 + cryptoxanthin/12) showed a poor correlation with the 24HR data and also had the lowest calibration coefficient.…”
Section: Discussionsupporting
confidence: 80%
“…For unadjusted nutrients the validity and calibration coefficients tended to be higher for men than women, however after energy adjustment the differences between men and women were reduced (7) . In the NIH-AARP study, validity coefficients for energy-adjusted nutrients ranged from 0·36 to 0·76, and the calibration coefficients from 0·24 to 0·68, which compared well with results of three other validation studies reviewed by the authors (28)(29)(30) and are slightly lower than the ranges that we observed in Australian-born participants; although all these studies are likely to overestimate the validity of the test instrument. Among the Australian-born, intakes of retinol equivalents (defined as vitamin A expressed as retinol equivalents = retinol + β-carotene/6 + α-carotene/12 + cryptoxanthin/12) showed a poor correlation with the 24HR data and also had the lowest calibration coefficient.…”
Section: Discussionsupporting
confidence: 80%
“…25,30 In general, the CC computed for each nutrient in the present study were similar or slightly lower than the ones reported in other validation studies carried out among adolescent [26][27][28] and adult population. [22][23][24][25]30 In our study, the average PCC, between SFFQ and two 24DRs, for absolute nutrient intake was 0.365 for adults and 0.374 for adolescents. For both adults and adolescents, corrections by energy adjustment increased the observed CC for some nutrients, but decreased the CC for the majority.…”
Section: Validity Of a Food Frequency Questionnaire To Assess Food Insupporting
confidence: 42%
“…20,[22][23][24][25][26][27][28] This possibly results when people ; the average of two 24 hour dietary recalls ‡ All nutrients were log-transformed § The energy-adjusted correlations between dietary methods use the residuals from regressing each nutrient on the total calories (residual method) # The deattenuated correlation coefficient was calculated using the ratio of the within-to between-person variance measured from the 24DRs. The formula used to calculate the corrected correlation was: r c = r o √1+λ/n where r c is the corrected correlation between the energy adjusted nutrient, r o is the observed correlation, λ is the ratio of within-and between-person variances, and n is the number of replicated recalls (n=2) & P-value <0.001 ≠ P-value <0.01 ∞ P-value <0.05 ø Not significant…”
Section: Discussionmentioning
confidence: 99%
“…The FFQ includes >135 food items that all relate to the diet during the previous year in ten categories: fruits and juices; vegetables and grains; meat, poultry, eggs and fish; mixed dishes; breads, salty snacks, spreads; breakfast cereals; sweets; dairy products; beverages; and foods to be added. The FFQ has been validated against 24-hour recall data [53,54]. Upon completion of the FFQ, a registered dietitian individually reviewed the FFQ, and any discrepancies/questions were addressed.…”
Section: Assessment Of Energy and Fat Intakementioning
confidence: 99%